Pelatihan Bendahara Desa Mahir Pajak di Kecamatan Lape Kabupaten Sumbawa - Diah Intan Syahfitri; Denny Hambali; Reza Muhammad Rizqi; Arya Zulfikar Akbar (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Training and mentoring of village treasurer to proficient in taxes is carried out with the aim to increase knowledge of villages officials, especially for villages heads, village treasurer, village supervisor as well as businessmen and local communities on tax regulations and tax reporting procedures. So, implementation of this activity is expected so that village can optimize managing of village tax revenue, ensure compliance with tax regulations, as well as support the development and overall welfare of the village. In this soscialization activity, explained about some knowledge and tax regulations as well as providing interactive and practical sessions to the participants.  Furthermore, provide assistance on how to fill out tax reporting forms in accordance with tax provisions that apply to tax payers in Lape district, Sumbawa regency.